Integrated Pest Management to control Varroa destructor and its implications to Apis mellifera colonies - Ruffinengo, Sergio Roberto (2014)
Integrated Pest Management (IPM) is a pest management system that, in the socioeconomic context of farming systems, the associated environment and the population dynamics of the pest species, utilizes all suitable techniques in a compatible manner as possible to maintain the pest population levels below those causing economic injury. This article covers the principal aspects of the interaction between Apis mellifera and Varroa destructor and it describes the classical control forms applied to reduce the mite negative impact on colonies. Some examples of IPM activities that have been done to control this parasite in the southeast of Buenos Aires province, Argentina have shown good results. Several products worldwide have shown good effectiveness as well. Nevertheless, there are certain risks and hazards inherent to their use, such as: their negative impact on human health, resistance phenomena, loss of beneficial insects and native fauna, environmental pollution and drug residues in the hive products harmful for human consumption. The development of acaricide resistance in V. destructor populations and the possibility of incorporating contaminants in colonies by means of this type of treatment have promoted the addition of new molecules to minimize these disadvantages. The application of organic acids, essential oils and their components have become a worthwhile alternative. It can be concluded that to achieve an integrated management of V. destructor entails a change of mind for beekeepers and the active participation of all actors involved in the beekeeping sector to promote scientific activities aimed to discovering and developing new tools to be incorporated in an IPM Program against V. destructor.